2016
DOI: 10.1007/s10072-016-2710-y
|View full text |Cite
|
Sign up to set email alerts
|

The expression of miRNA-221 and miRNA-222 in gliomas patients and their prognosis

Abstract: The aim of this study is to explore the expression of microRNA (miRNA)-221 and miRNA-222 in human glioma cells and tissues. The expression of miRNA-221 and miRNA-222 in human glioma cell line U87, U251, A172, LN229 and surgery resected glioma tissues were measured. The survival rate of X-ray (2 Gy) irradiated glioma cells were calculated. 165 cases of glioma patients were recruited successfully; the expression of miRNA-221 and miRNA-222 in their resected tissues were measured. The expression of miRNA-221 and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Glioma is an aggressive tumor and the average survival time in patients with high-grade glioma is not more than one year. [27][28][29][30] Sev was reported to be involved in the regulation of glioma progression 4,31 and our data showed that Sev inhibited glioma progression in vitro and tumor growth in vivo. However, the current studies were mostly focused on the regulatory mechanisms of miRNAs and long noncoding RNAs in Sev-mediated human diseases.…”
Section: Discussionsupporting
confidence: 59%
“…Glioma is an aggressive tumor and the average survival time in patients with high-grade glioma is not more than one year. [27][28][29][30] Sev was reported to be involved in the regulation of glioma progression 4,31 and our data showed that Sev inhibited glioma progression in vitro and tumor growth in vivo. However, the current studies were mostly focused on the regulatory mechanisms of miRNAs and long noncoding RNAs in Sev-mediated human diseases.…”
Section: Discussionsupporting
confidence: 59%
“…A large number of studies have reported that certain miRNA are involved in the regulation of tumor progression, and may have tumor-promoting or tumor-suppressive roles with regard (25)(26)(27). miRNAs may be used as prognostic indicators and therapeutic targets in gliomas (28,29). In the present study, comprehensive miRNA profiling of high-grade vs. low-grade gliomas was performed by microarray analysis.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Nie S. et al demonstrated that miR-495 induced the change of metabolism in glioma cells by increasingly Glut1 expression, resulting in the increase of glucose-taking and glioma developing [14]. MiRNA-221 and miRNA-222 were found to be highly expressed in glioma and the expression of which was closely related to survival rates of glioma cells [15]. Herein we provided an insight into the relationship of glioma and another miRNA, miR-338-3p, which have been discovered essential in the development of non-small-cell lung carcinoma, ovarian epithelial carcinoma, and gastric cancer [16][17][18].…”
Section: Micrornas (Mirnas) Another Family Of Non-codingmentioning
confidence: 99%